2020
DOI: 10.3390/brainsci10070412
|View full text |Cite
|
Sign up to set email alerts
|

Function-Based Tractography of the Language Network Correlates with Aphasia in Patients with Language-Eloquent Glioblastoma

Abstract: To date, the structural characteristics that distinguish language-involved from non-involved cortical areas are largely unclear. Particularly in patients suffering from language-eloquent brain tumors, reliable mapping of the cortico-subcortical language network is of high clinical importance to prepare and guide safe tumor resection. To investigate differences in structural characteristics between language-positive and language-negative areas, 20 patients (mean age: 63.2 ± 12.9 years, 16 males) diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Therefore, two hypotheses can be formulated to support the interaction of posterior MFG and area 55b with both streams of language: a direct connectivity via relay of some subcomponents of both AF and IFOF and an indirect connectivity via the stimulation of U-fibers to the adjacent gyri (IFG and SMA). In addition to previous imaging and dissection data, recent nTMS data support a strong connectivity of language positive sites via the U-fiber system, supporting the indirect connectivity theory ( 52 ). The strong connectivity to the primary motor cortex further supports the potential role for hand movement integration in language ( 43 ) and the involvement of this area in the articulation and praxis of speech ( 9 ).…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, two hypotheses can be formulated to support the interaction of posterior MFG and area 55b with both streams of language: a direct connectivity via relay of some subcomponents of both AF and IFOF and an indirect connectivity via the stimulation of U-fibers to the adjacent gyri (IFG and SMA). In addition to previous imaging and dissection data, recent nTMS data support a strong connectivity of language positive sites via the U-fiber system, supporting the indirect connectivity theory ( 52 ). The strong connectivity to the primary motor cortex further supports the potential role for hand movement integration in language ( 43 ) and the involvement of this area in the articulation and praxis of speech ( 9 ).…”
Section: Discussionsupporting
confidence: 64%
“…This Special Issue entitled "Modern Developments in Transcranial Magnetic Stimulation (TMS)-Applications and Perspectives in Clinical Neuroscience" in Brain Sciences received studies covering various applications of TMS, with focuses on neuronavigated TMS (nTMS) for mapping of cortical functions [10][11][12][13][14], treatment and modulatory effects [15][16][17][18][19], and basic neuromechanisms [20][21][22], all clinically relevant and supporting the aims set for the Special Issue.…”
mentioning
confidence: 93%
“…Their results provided additional and new evidence in patients with glioblastoma multiforme regarding the connection of speech and language function and brain anatomy, with nTMS demonstrating that responsiveness to stimulation is critically related to cortical and subcortical interplay and the rate of speech impairment [14]. They considered that the results further increase confidence in nTMS language mapping and nTMS-based tractography in the clinical setting [14]. In their study, Baro et al reported a case of nTMS-based tractography application in neurosurgery in a bilingual patient affected by a brain tumor in the left temporal lobe, who underwent nTMS mapping for both languages (Romanian and Italian) [10].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The FA is a measure for the directedness of diffusion, with values between 0 and 1, and is low in fluids and high in fiber bundles [ 11 ]. In iPlan Cranial 3.0 (Brain Lab AG, Munich, Germany), a prevalent software tool for neurosurgical planning, the standard cutoff is set to 0.3 [ 12 , 13 , 14 ]. In recent studies, this cutoff has been individually determined by a structured process of trial and error, with the lowest value at 0.1 [ 6 , 15 ].…”
Section: Introductionmentioning
confidence: 99%